Elevated serum β-d-glucan levels in cavitary pulmonary nocardiosis. Issue 7 (22nd July 2020) - Yagyu, Kyoko; Nakatsuji, Yuko; Matsushita, Haruhiko
Abstract : An 86-year-old woman with Borrmann type III colorectal cancer (Union for International Cancer Control pT4aN2bM1c, pStage IVc) had received dexamethasone for the last 6 months as palliative care. She presented with a low-grade fever, chest pain and cough. Chest radiography on admission showed cavities and consolidations bilaterally in the upper lobes. A blood examination on admission revealed highly elevated serum β-d-glucan levels. The diagnosis by bronchoscopy was pulmonary nocardiosis. With trimethoprim/sulfamethoxazole and imipenem/cilastatin, the β-d-glucan levels were decreased, and chest X-ray showed improvement after 1 month. β-d-glucan is known to be a biomarker of fungal infection. It is possible that β-d-glucan levels also indicate a pulmonary infection by Nocardia .